Decoration of Fibrin with Extracellular Chaperones - Talens, Simone; Leebeek, Frank W. G.; Veerhuis, Robert; Rijken, Dingeman C. (Thrombosis and Haemostasis, 2019)
Background Many proteins bind to fibrin during clot formation in plasma. We previously identified by mass spectrometry the most abundant proteins that noncovalently bind to fibrin clots. Several of these proteins (e.g., apolipoprotein J/clusterin, haptoglobin, α2-macroglobulin, α1-antitrypsin) can act as extracellular chaperones.Objective We hypothesize that clot-binding proteins may interact with fibrin as chaperones. The goal of this study is to test this hypothesis and to investigate the origin of the cross-β or amyloid structures in fibrin clots, which are associated with protein unfolding.Methods and Results A thioflavin T assay was used to detect cross-β structures. A steadily increasing amount was measured in the fibrinogen fraction of plasma during heat stress, a standard treatment to induce unfolding of proteins. Heat-stressed plasma was clotted and clot-bound proteins were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The results showed that the amounts of the clot-bound proteins were related to the duration of the heat stress. This indicates that cross-β structures in unfolded fibrin(ogen) are involved in clot binding of the proteins, which supports our chaperone hypothesis. A contributing role of fibrin formation itself was studied by clotting purified fibrinogen with thrombin in the presence of thioflavin T. The fluorescence intensity increased in time in the presence of thrombin, but did not increase in its absence. This provides evidence for the generation of cross-β structures during fibrin formation.Conclusion Fibrin clots generated in plasma are decorated with extracellular chaperones. The binding of these chaperones involves cross-β structures originating both from unfolded fibrinogen and from fibrin formation.
Keywords: amyloid structure; blood coagulation; extracellular chaperones; fibrin; fibrinogen